The Role Of Companies’ Growth Analysis In Evaluating Their Financial Performance: With A Case Study - Ennemri Nasreddine (My University, 2019)
Abstract: This research aimed to show how to evaluate the financial performance of companies using the indicators issued from growth analysis. The research focused on tow companies working in Algeria which are: EL-AURASSI hotel and NCR ROUIBA specialized in juice production. The study concluded the difference of performance realized by the tow companies is due mainly to the difference of the compatibility that should be kept between the value of capital employed and the volume of sales. ملخص: هدف البحث إلى استعراض كيفية تقييم الأداء المالي بالاستناد إلى المؤشرات المنبثقة من تحليل نمو المؤسسة. وقد سلط البحث الضوء على مؤسستين ناشطتين في الجزائر هما: فندق الأوراسي ومؤسسة مشروبات رويبة. وخلص البحث إلى أن التفاوت في أداء الشركتين إنما يعود بالدرجة الأولى إلى اختلافهما في إحداث التوازن المطلوب بين قيمة الأموال المستثمرة وحجم رقم الأعمال المحقق.
Keywords: growth ; performance ; financial performance ; performance evaluation ; growth analysis